2013
DOI: 10.1111/eva.12068
|View full text |Cite
|
Sign up to set email alerts
|

Small effective size limits performance in a novel environment

Abstract: Understanding what limits or facilitates species' responses to human‐induced habitat change can provide insight for the control of invasive species and the conservation of small populations, as well as an arena for studying adaptation to realistic novel environments. Small effective size of ancestral populations could limit the establishment in, or response to, a novel or altered habitat because of low genetic variation for ecologically important traits, and/or because small populations harbor fixed deleteriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 56 publications
0
24
1
Order By: Relevance
“…Shorter‐lived scrub endemics of the same region, such as Hypericum cumulicola and Paronychia chartacea (Quintana‐Ascencio, Weekley & Menges ; Schafer et al . ; Oakley ), experienced higher fecundity but more variable survival in roadsides. Higher survival rates in L. ohlingerae and increasing fecundity in roadsides may result from decreased competition in this human‐disturbed habitat (Petrů & Menges ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shorter‐lived scrub endemics of the same region, such as Hypericum cumulicola and Paronychia chartacea (Quintana‐Ascencio, Weekley & Menges ; Schafer et al . ; Oakley ), experienced higher fecundity but more variable survival in roadsides. Higher survival rates in L. ohlingerae and increasing fecundity in roadsides may result from decreased competition in this human‐disturbed habitat (Petrů & Menges ).…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic disturbance along sandy roads can increase fecundity, likely due to reduced below‐ground competition, and population instability (Quintana‐Ascencio, Weekley & Menges ; Schafer et al . ; Oakley ). Anthropogenic disturbances can also interact with other drivers, such as herbivory and fire, in affecting populations.…”
Section: Introductionmentioning
confidence: 99%
“…By examining the performance of multiple populations in natural common gardens and reciprocal transplants, however, we were able to further clarify some aspects of the relationship between population size and performance. Common garden experiments allowed us to control for confounding effects if fitness is only examined observationally in each population's native environment (Oakley ) or through home‐away comparisons. Similar to our home versus away analysis, we found that large populations tended to exhibit improved performance in their native environments relative to novel environments.…”
Section: Discussionmentioning
confidence: 99%
“…Small populations either (i) outperformed large populations (Hooftman et al. ), (ii) exhibited no loss of fitness or were outperformed by larger populations only in more benign environmental conditions (Oakley ), or (iii) exhibited reduced performance in increasingly dissimilar environments relative to their native environment (Bowman et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…As gene flow between populations decreases, genetic drift may also cause populations to become differentiated from one another (Ledig et al, ; Gemmill et al, ; Young & Clarke, ). Small populations are also vulnerable to environmental stochasticity, catastrophe, and loss of habitat to human activities (Ouborg et al, ; Oakley, ), resulting in reduced capacity for adaptation to changing conditions (Willi et al, ). Rare, endemic plant species with edaphic specializations are especially vulnerable to extinction or extirpation due to loss of habitat and subsequent population size reduction (Frankham, ; Leimu et al, ; Reed, ; Gordon et al, ).…”
mentioning
confidence: 99%